THE INFLUENCE OF ENVIRONMENT, E-WOM, AND FACILITIES ON TOURIST DECISIONS TO VISIT SAWUEK RIVER, NORTH ACEH, INDONESIA - Rusydi, Rusydi; Adnan, Adnan; Sutan, Sutan; Bachri, Naufal (RADJA PUBLIKA, 2021)
This study examined the effect of the environment, E-WOM, and facilities on tourists' decision to visit Sawuek river, Indonesia. This study obtained the data by distributing questionnaires to 251 respondents selected using the non-probability approach, namely purposive sampling. The data were analyzed using the Amos SEM tool. The results showed that the environment, E-WOM, and facilities had a positive and significant effect on the decision of tourists to visit the Sawuek river in Indonesia. The tourism environment was the dominant variable influencing tourist decisions. This study had implications for the development of the concept of a river tourism environment.